2015
DOI: 10.1007/s00345-015-1750-x
|View full text |Cite
|
Sign up to set email alerts
|

Which factors affect the hospital re-admission and re-hospitalization after flexible ureterorenoscopy for kidney stone?

Abstract: We found that inability to achieve stone-free status predicted HR and re-hospitalization, while postoperative complication and prolonged hospitalization also predicted re-hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
3
2
Order By: Relevance
“…Similarly, in literature there are studies showing that a high ASA score is a risk factor for re-presentation after discharge and for postoperative infection. 7,14 Although some studies in literature have shown high rates of patients with a CCI score of >2 re-presenting after discharge and being readmitted to hospital, the CCI scores in the current study were similar in both groups. 14 When literature was examined in respect of the effect of a history of stone surgery on infective complications, there were seen to be studies showing that a history of stone surgery was a risk factor for infective complications; and there were studies where previous surgery was not seen as a risk factor.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Similarly, in literature there are studies showing that a high ASA score is a risk factor for re-presentation after discharge and for postoperative infection. 7,14 Although some studies in literature have shown high rates of patients with a CCI score of >2 re-presenting after discharge and being readmitted to hospital, the CCI scores in the current study were similar in both groups. 14 When literature was examined in respect of the effect of a history of stone surgery on infective complications, there were seen to be studies showing that a history of stone surgery was a risk factor for infective complications; and there were studies where previous surgery was not seen as a risk factor.…”
Section: Discussioncontrasting
confidence: 45%
“…7,14 Although some studies in literature have shown high rates of patients with a CCI score of >2 re-presenting after discharge and being readmitted to hospital, the CCI scores in the current study were similar in both groups. 14 When literature was examined in respect of the effect of a history of stone surgery on infective complications, there were seen to be studies showing that a history of stone surgery was a risk factor for infective complications; and there were studies where previous surgery was not seen as a risk factor. 6,7 In the analysis of the current study, previous renal stone surgery was not found to be a risk factor for infective complications.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The representation rate to ED of at least 15% is consistent with other reports. 15 The retrospective nature of this study prevents any review of the pre-operative decision making but the large number of cases allows a snapshot of current Australian practice regarding URS. It could be argued that the results of those patients not reviewed were much better and that an active decision was made not to arrange any review, but there is no evidence in the hospital records that such decisions were made.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary metrics used to measure the outcome of RIRS is the stone-free rate (SFR). Residual stone fragments (RSF) of 4 mm or less after RIRS are accepted as clinically insignificant 3 . RIRS studies have shown that in almost 20% of cases, clinically insignificant RSFs are observed postoperatively 4 ; however, these RSF may grow and cause stone-related events (SRE) such as pain and infection 5,6 .…”
Section: Introductionmentioning
confidence: 99%